2015
DOI: 10.1378/chest.14-2506
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Assessing Outcomes in Studies of Chronic Cough

Abstract: Validated and reliable cough-specific health-related QoL questionnaires are recommended as the measurement of choice to assess the impact of cough on patients. How they compare is yet to be determined. When used, the reporting of cough severity by visual analog or numeric rating scales should be standardized. Previously validated QoL questionnaires or other cough assessments should not be modified unless the new version has been shown to be reliable and valid. Finally, in research settings, tussigenic challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 101 publications
0
87
0
4
Order By: Relevance
“…All these instruments have been developed for chronic cough in a general population and are reviewed elsewhere [55]. Experience and validation of these tools in patients with IPF are limited (table 2 provides an overview).…”
Section: Assessment Of Cough In Ipfmentioning
confidence: 99%
“…All these instruments have been developed for chronic cough in a general population and are reviewed elsewhere [55]. Experience and validation of these tools in patients with IPF are limited (table 2 provides an overview).…”
Section: Assessment Of Cough In Ipfmentioning
confidence: 99%
“…Numerous studies were performed to define clinical tools for measurement of cough. Among them, there are cough monitors, cough specific quality of life questionnaires, VAS and sensitivity to inhaled cough irritants measured in cough challenge test [9,10]. To follow the effect of speech therapy in our patient, we used the above mentioned tools with the exception of cough monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Before initiation of speech therapy, cough severity and its influence on quality of life was assessed in accordance with ERS guidelines [9]. We applied Visual Analogue Scale (VAS) for subjective assessment of cough severity and Leicester Cough Questionnaire (LCQ) for evaluation of influence of cough on patients' quality of life [9,10]. Moreover, cough challenge test with capsaicin was performed to assess the sensitivity to inhaled irritants [9,10].…”
Section: Case Reportmentioning
confidence: 99%
“…We established a strong correlation among the domains of the questionnaire, but a weak correlation between the LCQ and cough VAS. The other studies demonstrated that correlation with cough specific VAS varied widely from study to study, but showed robust results [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness was analysed by calculating the 95% confidence interval for the average improvements in the three domain scores and the total score of the LCQ. [7][8][9][10][11][12][13][14][15][16].…”
Section: Validationmentioning
confidence: 99%